O efeito do Sped nos serviços profissionais de contabilidade na percepção de gestores de escritórios contábeis na cidade do Rio de Janeiro - Anjos, Emmanuel Lopes dos (2018)
The objective of the study: In 2007, the Federal Government, through Law 6.022, on January 22, 2007, establishes the Public Digital Bookkeeping System (SPED). SPED is part of a set of initiatives launched by the Federal Government, within the Growth Acceleration Program (PAC), and the set of initiatives aimed at bringing efficiency to the government manager from the New Public Administration. In this way, this paper aims the objective to identify the perception of accounting office managers regarding the effects in relation to the increase in service, the need for investment, the qualification of personnel and the impact of new services in the departments of accounting, fiscal, department personal, computer and financial services in their offices through the need to meet SPED obligations of their clients. Design/Methodology/Approach: This work is classified as qualitative research, organized through multiple case studies. To make this work, we used an exploratory and descriptive survey model. The survey sample was developed in a non-probabilistic manner, in which eleven accounting offices were selected from the city of Rio de Janeiro. We choose these offices following the researcher's professional and personal relationship. The questions were directed to the partners and main managers of these offices, as they are individuals with direct interest and responsibility to clients, governmental authorities and others stakeholders accounting offices. Results: It was observed that the SPED service initially brought to the office's needs for investments in systems and people. The SPED Attendance led to accounting offices rework, increased costs related to overtime, need for hiring more qualified staff and investment in systems and information technology. Many of the costs and overtime revealed in the research are due not only to the SPED program but also to problems related to system parameterization. In general, the costs and investments in accounting offices have not yet been transformed into opportunities for new lines of services and revenue growth. On the other hand, it was perceived by the partners and managers of the accounting offices consulted that SPED brought greater security about information security and its quality since SPED created an environment less conducive to fraud risks. And continued investment in systems and people can bring a better value-added service environment and fewer manual jobs still run by these offices. Practical implications: This work has practical implications for the partners and managers of the accounting services offices because, regardless of their size and time of existence, it provides a view of the common investment needs in these accounting offices given the need to attend SPED. It is important to point out that the strategy of crossing and electronic data research (where the SPED is based) by the landowning authorities in Brazil is an irreversible trend. In this way, current and future entrepreneurs and accounting managers should prepare and remain prepared for this scenario. Overall, the research led to the conclusion that many of the problems revealed are due to the need to improve the systemic parameterization of accounting offices. Originality and contributions: The advent of SPED is just over ten years old, and the SPED environment has been reformulating more and more. The present paper presents a current view of the scenario of the impact of SPED to accounting offices, showing that there is not a considerable number of surveys regarding the impact in this group of service providers. In addition to what has already been reported, this paper indicates that, although the investments in personnel and technology have not been perceived as being rewarded by the generation of new services and revenue lines, the need to continue to invest in people and technologies through SPED can generate an environment conducive to the advent of future innovations in the business of accounting services to be studied in future research in this regard.